Recent Trends in Surgical Approach to Thyroid Cancer - Rossi, Leonardo; Materazzi, Gabriele; Bakkar, Sohail; Miccoli, Paolo (Frontiers in Endocrinology, 2021)
Over the past decade, the incidence of thyroid cancer has rapidly increased worldwide and thyroid surgery has become one of the most common performed surgical procedures. Even though conventional open thyroidectomy remains the gold standard, this approach leaves a neck scar which could be worrying mainly for young women. The recent progress in surgical technology, as well as patient cosmetic requests, have led to the development of alternative access to the thyroid lodge. Thus, alternative techniques have been established in order to potentially provide a more appealing cosmetic result, both with a minimally-invasive cervical or remote-access approach. However, the introduction of these new techniques was initially approached with caution due to technical challenges, the introduction of new complications and, above all, skepticism about the oncologic effectiveness. Among several alternative approaches proposed, the minimally invasive video-assisted thyroidectomy and the robot-assisted transaxillary thyroidectomy became popular and obtained the favor of the scientific community. Moreover, the recent introduction of the trans-oral endoscopic thyroidectomy with vestibular approach, although the safety and the efficacy are still under discussion, deserves particular attention since it represents the only technique truly scarless and provides the best cometic result. The purpose of this article is to provide an overview of the current main alternative approaches for the treatment of thyroid cancer with particular focus on the oncological effectiveness of the procedures.